(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2024)
This article analyzes how hiring practices affect the caliber of production workers in manufacturing companies. It examines different hiring practices, such as internal promotions, recommendations, and outside platforms, and assesses how they affect worker productivity, retention, and performance. It also demonstrates through surveys and case studies how improving staff quality and operational efficiency may be achieved by matching recruitment tactics with business objectives. The results offer suggestions for improving hiring procedures in order to boost output in manufacturing environments.